Design of an Elementary Electric Clay Stove - Bwambale, Festo (Kabale University, 2025)
This project proposal focuses on the design and development of an elementary electric clay stove tailored to the needs of Kabale Municipality, aiming to address the specific cooking challenges and opportunities within this region. Traditional clay stoves, while culturally integral and cost-effective, commonly rely on biomass fuels, contributing to indoor air pollution and deforestation. By incorporating electric heating technology, this initiative proposes a sustainable alternative that leverages Kabale’s increasing access to electricity, reducing environmental impact and enhancing household health. The project will engage local artisans in the design process to ensure that the stove is culturally appropriate and economically viable. It will include material testing for optimal thermal efficiency, prototype development, and community-based trials to evaluate user experience and stove performance. The anticipated outcome is the widespread adoption of a clean, efficient, and locally produced cooking solution that aligns with the environmental and socio-economic context of Kabale Municipality